Kurang Tegasnya Pendeta Mendisiplin Anggota Jemaat dalam Kasus Penyebaran Berita Palsu atau Hoaks - Deisy Agustina Tinangon; Beni Chandra Purba; Budi Kelana (PT. Penerbit Tiga Mutiara, 2024)
This research investigates the challenge posed by the perceived lack of assertiveness among pastors in disciplining members of the congregation amidst the proliferation of fake news or hoaxes. It delves into the multifaceted roles of pastors within the church context, the nuanced concept of discipline as it pertains to congregational dynamics, and the pervasive phenomenon of hoaxes in contemporary society. Emphasizing the critical importance of pastors taking proactive measures to address and counteract the dissemination of hoaxes to safeguard the integrity and unity of the church community, this paper employs a comprehensive descriptive research methodology. Through an in-depth exploration of the characteristics and implications of hoaxes, the functions and responsibilities of pastors, and the significance of discipline within the ecclesiastical setting, this study aims to provide valuable insights into the complexities of managing misinformation within religious communities. By synthesizing theoretical frameworks and empirical observations, the paper offers actionable recommendations for pastors to effectively combat hoaxes while fostering an environment of truth, trust, and integrity within the church.